Insights Regarding the Applicability of the Defining Issues Test to Advance Ethics Research with Accounting Students: A Meta-analytic Review - Christensen, Anne L. (Journal of business ethics, 2016)
Numerous researchers have investigated accounting students’ levels of moral reasoning, ethical choice and judgment employing the Defining Issues Test (DIT) and using its P score as an indicator of moral reasoning. Not surprisingly, a number of DIT studies report conflicting results. Moreover, despite widespread use of the DIT, there is concern that it may not adequately measure all facets of ethical judgment (cf. Bailey et al., Behav Res Account 22(2):1–26, 2010). Thus, we endeavor to provide insight not only into the contradictory results but also about the applicability of the DIT for studying accounting students. To do so, we collect published and unpublished DIT studies employing accounting students as subjects and use meta-analysis to aggregate findings across these studies to quantify their results, examining commonly employed variables. We show significant relationships between P scores and some variables (length of professional experience, choice of major, political ideology, gender, GPA and education level) but not others (age). Further, our findings demonstrate that the DIT provides added insights when exploring questions of ethical choice, and ethics instruction, particularly when the instruction is embedded in an accounting course. Finally, we find that the level of DIT P scores reported in the studies relates to whether the study was published. We discuss the implications of our findings for future research.